Ultra-sensitive method based on time-resolved fluorescence immunoassay for detection of sulfamethazine in raw milk. Issue 1 (1st January 2018) - Hu, Song; Li, Danhong; Huang, Zhen; Xing, Keyu; Chen, Yuan; Peng, Juan; Lai, Weihua
ABSTRACT: A novel lateral flow assay (LFA) was developed by introducing Eu (III)-doped polystyrene nanoparticles (EuNPs) for rapid and ultra-sensitive detection of sulfamethazine (SM2 ) in raw milk. The limit of detection and linear range of the proposed method were 0.0045 and 0.05–10 ng/mL, respectively. The recovery of LFA for the detection of SM2 in raw milk was 96.1–108.2%. The proposed LFA provides a rapid and convenient strategy for fast and ultra-sensitive screening of SM2 in raw milk. EuNP-LFA may be a remarkable method for the detection of other targets at low concentrations to ensure food safety. GRAPHICAL ABSTRACT: UF0001